Sisa hidup / Atifah Othman - Othman, Atifah (Universiti Teknologi MARA, Kedah, 2024)
Anthology of 200 poems which were contributed by lecturers and academicians from UiTM and other higher learning institutions. This is in fact the largest collection of poems compiled in one anthology.